2020
DOI: 10.1111/ijlh.13306
|View full text |Cite
|
Sign up to set email alerts
|

Complex biological patterns of hematology parameters in childhood necessitating age‐ and sex‐specific reference intervals for evidence‐based clinical interpretation

Abstract: Introduction: Hematology laboratory parameters are among the most routinely ordered tests in support of adult and pediatric care. However, appropriate interpretation of test results has been a challenge in pediatrics since accurate and up-to-date reference intervals that reflect the dynamic physiological changes associated with growth and development have not been available. Critical gaps continue to exist in pediatric hematology reference intervals for modern laboratory platforms. To address this gap, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
(134 reference statements)
5
33
0
Order By: Relevance
“…Second, the geographic and ethnic composition of the analyzed cohorts varies. For example, we compare reference intervals obtained for children in Canada (CALIPER studies 31 35 ), the US 40 , Austria 36 , and Germany 37 . Third, the time range of measurement and measurement sites differ leading to potential time- and site-specific effects although we compared only studies using Roche cobas or Sysmex instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the geographic and ethnic composition of the analyzed cohorts varies. For example, we compare reference intervals obtained for children in Canada (CALIPER studies 31 35 ), the US 40 , Austria 36 , and Germany 37 . Third, the time range of measurement and measurement sites differ leading to potential time- and site-specific effects although we compared only studies using Roche cobas or Sysmex instruments.…”
Section: Discussionmentioning
confidence: 99%
“…For these biomarkers, we estimated reference intervals using refineR and kosmic with N = 200 bootstrap iterations and compared the results to reference intervals obtained from different direct method studies from literature 31 – 40 . The comparison studies include reference intervals obtained as part of the CALIPER project ( CA nadian L aboratory I nitiative in PE diatric R eference Intervals) 31 35 , package inserts accompanying the analytical devices 38 – 40 , a study obtained on a German pediatric cohort 37 and one carried out in an Austrian adolescent cohort 36 . Sample sizes in comparison studies were between 26 and 1872 (median: 200).…”
Section: Methodsmentioning
confidence: 99%
“…20 Study participation from community clinics has been described in detail by previous CALIPER studies. 20 Briefly, community participation involved completion of a health questionnaire and a blood donation following informed consent. Inclusion criteria included nonpregnant children and adolescents from birth to 18 years of age.…”
Section: Participant Recruitment and Sample Acquisition And Analysismentioning
confidence: 99%
“…20 Instrument performance was monitored through routine quality control practices and was concurrently used for clinical care, passing all manufacturer and hospital specifications. Quality control data for each parameter throughout study duration can be found in the Supplemental Material of Bohn et al 20…”
Section: Participant Recruitment and Sample Acquisition And Analysismentioning
confidence: 99%
“…Diffusion capacity of the lung for carbon monoxide (DLCO) was assessed by single-breathtechnique (MasterScope Spirometer and Master Screen Body, Jaeger/CareFusion, Höchberg); in all leukemia participants, DLCO was corrected for hemoglobin. Participants in the control group were derived from former studies: as we did not draw blood in those studies, hemoglobin was calculated according to existing normal values [20,21] and DLCO corrected for this hemoglobin value. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and effective resistance (Reff ) were reported as %predicted [22].…”
Section: Pulmonary Function Testingmentioning
confidence: 99%